Key developments and hotspots of exosomes in Alzheimer’s disease: a bibliometric study spanning 2003 to 2023 - Liu, Siyu; Geng, Daoying (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is a degenerative illness of the central nervous system that is irreversible and is characterized by gradual behavioral impairment and cognitive dysfunction. Researches on exosomes in AD have gradually gained the attention of scholars in recent years. However, the literatures in this research area do not yet have a comprehensive visualization analysis. The aim of this work is to use bibliometrics to identify the knowledge constructs and investigate the research frontiers and hotspots related to exosomes in AD.From January 2003 until June 2023, we searched the Web of Science Core Collection for literature on exosomes in AD. We found 585 papers total. The bibliometric study was completed using VOSviewer, the R package "bibliometrix," and CiteSpace. The analysis covered nations, institutions, authors, journals, and keywords.Following 2019, the articles on exosomes in AD increased significantly year by year. The vast majority of publications came from China and the US.